Improvement in patient-reported outcomes after lung transplantation is not impacted by the use of extracorporeal membrane oxygenation as a bridge to transplantation - Kolaitis, Nicholas A.; Soong, Allison; Shrestha, Pavan; Zhuo, Hanjing; Neuhaus, John; Katz, Patti P.; Greenland, John R.; Golden, Jeffrey; Leard, Lorriana E.; Shah, Rupal J.; Hays, Steven R.; Kukreja, Jasleen; et al. (The Journal of thoracic and cardiovascular surgery, 2018)
Extracorporeal membrane oxygenation (ECMO) is increasingly used as a bridge to lung transplantation. The impact of preoperative ECMO on health-related quality of life (HRQL) and depressive symptoms after lung transplantation remains unknown, however. In a single-center prospective cohort study, we assessed HRQL and depressive symptoms before and at 3, 6, and 12 months after lung transplantation using the Short Form 12 Physical and Mental Component Scores (SF12-PCS and SF12-MCS), Airway Questionnaire 20-Revised (AQ20R), EuroQol 5D (EQ5D), and Geriatric Depression Scale (GDS). Changes in HRQL were quantified by segmented linear mixed-effects models controlling for age, sex, diagnosis, preoperative forced expiratory volume in 1 second, 6-minute walk distance, and Lung Allocation Score. We compared changes in HRQL among subjects bridged with ECMO, subjects hospitalized but not on ECMO, and subjects called in for transplantation as outpatients. Out of 189 subjects, 17 were bridged to transplantation with ECMO. In all groups, improvements in HRQL following lung transplantation exceeded the minimally clinically important difference using the SF12-PCS, AQ20R, EQ5D, and GDS. HRQL defined by SF12-MCS did not change after transplantation. Improvements were generally similar among the groups, except for EQ5D, which showed a trend toward less benefit in the outpatients, possibly due to their better HRQL before lung transplantation. Subjects ill enough to require ECMO as a bridge to lung transplantation appear to achieve similar improvements in HRQL and depressive symptoms as those who do not. It is reassuring to both providers and patients that lung transplantation provides substantial improvements in HRQL, even for those patients who are critically ill in the run up to transplantation.